Cyclic Remodeling of the Nonhuman Primate Endometrium: A Model for Understanding Endometrial Receptivity - Slayden, Ov Daniel (Seminars in Reproductive Medicine, 2014)
Old World monkeys display physiological responses to steroid hormones that are similar to those of women. In this review, we describe cyclic morphological changes that take place within the uterus of Old World primates during the menstrual cycle. In primates, estrogen stimulates endometrial growth in the follicular phase of the menstrual cycle. Progesterone secreted in the luteal phase acts to induce secretory differentiation, which is required for successful embryo implantation. During the differentiation process, endometrial estrogen receptor-1 (ESR-1) is suppressed, and reduced staining for ESR-1 is a definitive marker of the onset of uterine receptivity. Downregulation of ESR-1 is topographically limited to the functionalis (upper) zones of the endometrium, the zones in which embryo implantation occurs, indicating that zone-specific factors play a role in the differentiation process. Future genomic and proteomic studies are expected to reveal additional markers for diagnosing endometrial receptivity. Due to the distinct zonal response of the endometrium to ovarian steroids, accurate histological characterization will remain necessary to interpret novel targets in the assessment of fertility.
Keywords: menstrual cycle; histology; endometrium; secretory differentiation; progesterone